Characterization of Rat ILCs Reveals ILC2 as the Dominant Intestinal Subset - Abidi, Ahmed; Laurent, Thomas; Bériou, Gaëlle; Bouchet-Delbos, Laurence; Fourgeux, Cynthia; Louvet, Cédric; Triki-Marrakchi, Raja; Poschmann, Jeremie; Josien, Régis; Martin, Jérôme (Frontiers in Immunology, 2020)
Innate lymphoid cells (ILCs) are tissue-resident lymphocytes that lack antigen-specific receptors and exhibit innate effector functions such as cytokine production that play an important role in immediate responses to pathogens especially at mucosal sites. Mouse and human ILC subsets have been extensively characterized in various tissues and in blood. In this study, we present the first characterization of ILCs and ILC subsets in rat gut and secondary lymphoid organs using flow cytometry and single cell RNA sequencing. Our results show that phenotype and function of rat ILC subsets are conserved as compared to human and mouse ILCs. However, and in contrast to human and mouse, our study unexpectedly revealed that ILC2 and not ILC3 was the dominant ILC subset in the rat intestinal lamina propria. ILC2 predominance in the gut was independent of rat strain, sex or housing facility. In contrast, ILC3 was the predominant ILC subset in mesenteric lymph nodes and Peyer patches. In conclusion, our study demonstrates that in spite of highly conserved phenotype and function between mice, rat and humans, the distribution of ILC subsets in the intestinal mucosa is dependent on the species likely in response to both genetic and environmental factors.